2004
DOI: 10.1007/s00420-004-0505-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute pulmonary toxicity following occupational exposure to a floor stain protector in the building industry in Switzerland

Abstract: Tilers should be warned against spraying floor stain repellents; there is also a need to make consumers aware that the spraying of waterproofing agents in a closed environment and concomitant smoking should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…First, the fluoropolymer may act as a carrier molecule allowing the hydrocarbon solvent to deeply penetrate alveoli [3]. Second, because of increased solvent volatility, the size of aerosol particles decreases more rapidly, resulting in increased inhalation and increased number of particles reaching the alveoli [7]. Third, the fluoropolymer resin may interact with type II alveolar cells and surfactant, generating acute lung injury [13].…”
Section: Discussionmentioning
confidence: 99%
“…First, the fluoropolymer may act as a carrier molecule allowing the hydrocarbon solvent to deeply penetrate alveoli [3]. Second, because of increased solvent volatility, the size of aerosol particles decreases more rapidly, resulting in increased inhalation and increased number of particles reaching the alveoli [7]. Third, the fluoropolymer resin may interact with type II alveolar cells and surfactant, generating acute lung injury [13].…”
Section: Discussionmentioning
confidence: 99%
“…An In Vitro Method for Predicting Inhalation Toxicity of Impregnation Spray Products Jorid B. Sørli 1 al., 1995;Lazor-Blanchet et al, 2004;Vernez et al, 2006). The potential health risk of impregnation products is well known, but pinpointing the causative agent that makes a product hazardous has proven difficult.…”
Section: Research Articlementioning
confidence: 99%
“…The symptoms often develop within minutes to a few hours after exposure and include coughing, shortness of breath and chest pain (Burkhart et al, 1996; Centers for Disease Control and Prevention, 1993). The symptoms spontaneously resolve within a few days, but sometimes supportive treatment with oxygen, bronchodilators or corticosteroids is needed (Burkhart et al, 1996;Laliberte et al, 1995;Lazor-Blanchet et al, 2004). Permanent effects after exposure are rare, but have been reported (Wallace and Brown, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Three occupational cases following the use of a stain-repellent resin on stone-tiled walls and floors were also reported. (15) The exposure conditions of these three cases were investigated in a previous study. (16) Emission measurements and simulations indicated that: (1) significant aerosol and solvent concentrations may occur during waterproofing, and (2) the amounts of solvent and particles in the workers' breathing zone were lower with the new resin formulation.…”
Section: Introductionmentioning
confidence: 99%